Pengaruh Komunikasi dan Penilaian Kinerja Terhadap Kepuasan Kerja Pengurus Pondok Pesantren Putra Tebuireng Jombang - Mucholifah Mucholifah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims to determine the effect of communication and performance appraisal on the job satisfaction of administrators at the Male of boarding school tebuireng jombang. The method used in this study is a quantitative research method and uses a causal or causal approach. The results showed that: (1) Communication did not influence partially on the job satisfaction of male boarding school tebuireng jombang administrators, (2) Performance evaluation partially influenced job satisfaction of male boarding school tebuireng jombang administrators, (3) Communication and performance appraisal influenced Simultaneous to the job satisfaction of the male boarding school boarder in Jombang.